Covid-19 vaccines, rules, deaths, and tourism recovery. (July 2022) - Okafor, Luke; Yan, Eric
Abstract: This study explores whether vaccination coverage, social distancing rules, and COVID-19 death rate affect tourism recovery using data from 249 countries/territories. We used panel data regression techniques—namely Fixed-effects, Hausman-Taylor, and Instrumental Variables regressions for the empirical analysis. Results show that a higher vaccination coverage is not necessarily accompanied by a higher tourism recovery. Similarly, a higher level of stringency restriction hinders tourism recovery. Results also indicate that a lower death rate helps to promote tourism recovery in developed economies. These results suggest that vaccination coverage alone is not the magic bullet for restarting the tourism industry. Policymakers should consider a mix of effective vaccination administration accompanied by the use of therapeutics to lower the COVID-19 death rate. Highlights: A higher vaccination rate alone is not accompanied by a higher tourism recovery. Death rate dampens tourism recovery significantly in developed economies. Stringency restrictions hinder tourism recovery. Lower risk of infection and death is necessary for the tourism industry to rebound.